BELAJAR BAHASA INGGRIS DITENGAH ISU RASISME MELALUI MEDIA WEBSITE - Yefta Christian; Robin Robin; Lenny Julyanti; Claudia Theophilia; Ferdinand William; Kevin Kevin; Michelle Febri Soegianto; Gracella Tandiono; Jeslyn Teo; Sani Kurnia; Vincent Gonawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
Batam City is an archipelago that is directly adjacent to Singapore and Malaysia, so English is an important language to learn. Also, English language education during schooling is uneven. The result is that not all people who are looking for work in Batam City can speak English fluently and fluently. Some of them are affected by discrimination, they can meet the requirements, but constrained in English. This program is designed to learn English through online media. The method used is a website platform that contains materials with a 5 Whys approach. The survey results show that the inability to speak English has become part of the discrimination and subject job seekers to considerable difficulties. So, the English learning program through this website platform helps the learning process of English independently and improves competence in English.